MildanBoimau HUBUNGAN PENGETAHUAN PERAWAT DENGAN PELAKSANAAN EARLY WARNING SCORE (EWS) PADA PASIEN DI RUANGAN EMERGENCY DAN INTENSIVE CARE UNIT (ICU) RUMAH SAKIT SILOAM KUPANG - Mildan Boimau (Cintra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2022)
Abstract Early Warning Score (EWS) is a system approach by scoring based on predetermined and adopted parameters. This Early Warning Score (EWS) is performed with the aim of assessing patients with acute conditions, early detection of deterioration in the patient's clinical condition during hospitalization, and initiating a competent timely clinical response. Early Warning Score (EWS) was carried out for all patients in the initial assessment with acute disease conditions and periodic monitoring of all patients who had a high risk of developing critical illness during their stay in the hospital. The purpose of this research is to know relationship between nurse’s knowledge and implementation of early warning system (EWS) in patients in emergency room and intensive care unit (ICU) at siloam hospital kupang. This is a quantitative research with correlational research type with cross-sectional approach. The sampling method used was a total sampling technique, amounting to 32 people. The instruments used were questionnaires and direct observation. The test used was the chi-square statistical test, p value = 0.002. This shows that p (0.002) <α (0.005) so that H0 is rejected and it can be stated that there is a significant relationship between the knowledge variable and the Early Warning Score (EWS) implementation variable in patients in the Emergency room and the Intensive Care Unit (ICU) room of RSU. Siloam Kupang. Good knowledge will tend to implement the Early Warning Score (EWS) properly and the services provided are more optimal. Key Words: Knowledge, Nurse, Early Warning System (EWS)